Alexithymia and its relation with emotional intelleigence for 6th grade students - انتصار كمال العاني عفراء حمزة الشمري (College of Education for Women, 2019)
This current study aims to: 1st: The recognizing of Alexithymia level for 6th grade students (Study Specimen) through the next Zero Hypothesis:1. There are no statistically significant differences at (0.05) level between the arithmetic mean of the specimen degrees as a whole and the central assumption for the scale of the lack in emotions expression 2. There are no statistically significant differences at (0.05) level between the arithmetic mean of the male students specimen and the arithmetic meanc of the female students specimen for the scale of Alexithymia. 2nd: ldentification the level of the emotional intelligence among 6th grade students (Study Specimen) through the next Zero Hypothesis: 1) There are no statistically significant differences at (0,05) level between the arithmetic means of the specimen degrees as a whole and the central means for the scale of emotional intelligence. . 2) 2-: There are no statistically significant differences at (0,05) level between the arithmetic means of the female students specimen degrees in the scale of emotional intelligence. 3rd: identifying the correlational relationship between the emotional intelligent ant the lack of emotions expression (Alxethymea). To achieve the study goals, the researchers prepared tow scales, one is (the scale of lack to motions expression according to Crtstal theory for this concept), and the other one is (the scale of emotional intelligence), then the researchers checked the validity and the reliability of the two scales and analyze the paragraphs statically, and after the analyze she applied the two scales on specimens that included (400) student of both genders from the six directorates (Al-Karkh and Al-Rusafa) located in Baghdad which they have been chosen in random stratified way . To analyze the results of the study, the researchers used a set of statistical methods such as (Tai test for one specimen and for two independent specimen, Pearson correlation coefficient, Hevah test, mono-variance analysis, mulyiple regeression analysis). Researcher's concluded the following results: a) The study specimen shows that (the 6th grade students) have Alexithymia in about average rate. b) It showed that there is a difference in emotions expression according to sex variable in favor of females among the study sbecimen on (the 6th grade students). c) .the study specimen showed for (6 th grade students) that they had an emotional intelligence. d) The results showsthat is no statistically significant for variables (theacademic achievement for the father, the academic achievement for the mother and the congenital ranking) in the specimen of the study (6th grade students). e) The resuts show that there is an inverse correctional relation betweenAlexithymia and the emotional intelligent in the specimen of the study (6th grade students).